Georgia Architectural and Historic Properties Survey of 211 Walnut St., Valdosta, Ga., December 1980 - Smith, Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of 211 Walnut St., Valdosta, Ga., December 1980. Bungalow style. Gabled tin roof with exposed rafters. Screened in gable porch. Interior chimney. Asbestos siding. Double hung sash windows with 2/2 lights. Set on brick piers. Fair condition. Date of Construction: App. 1910-1920. Significant as part of a potential N.R. district which would cover a 4 or 5 block area.
Georgia Architectural and Historic Properties Survey of 211 Walnut St., Valdosta, Ga., December 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 3 scans. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 78.6 MB (82,419,707 bytes).
Keywords: Historic buildings; Real property surveys; Lowndes County Historical Society (Lowndes County, Ga.); Valdosta (Ga.)